Udmurdi hällilaul: veel kord esmaallika probleemist - Irina Nurieva (Mäetagused)
Udmurt lullabies are divided into two different musical and stylistic groups. The first one, similar to many Finno-Ugric peoples, includes improvised songs - the most archaic layer of song folklore. Improvised Udmurt lullabies are various rhythmic and melodic intonations that are meant to soothe or put the child to sleep. However, the singers I met during fieldwork often sang another lullaby based on the verse of G. E. Vereshchagin, “Chagyr, chagyr dydyke...” (Blue, blue pigeon…). All the variants of this lullaby form the second group. That lullaby has been recorded throughout Udmurtia, almost supplanting local improvised lullabies. Musical analysis of the lullaby “Chagyr, chagyr dydyke...” has shown that, unlike improvised lullabies, this tune belongs to a late music style. The lyrics of the lullaby attracted the attention of philologists and literary critics, who tried to clarify the authorship of the verse. The verse “Chagyr, chagyr dydyke...” was published by the Udmurt writer and ethnographer Vereshchagin in 1889. The heated discussion around the problem of Vereshchagin’s authorship, which unfolded later on, lasted for several decades. Udmurt folklorist T. G. Vladykina put an end to the dispute, concluding that the author of the lullaby was Vereshchagin. As proof of his authorship, the researcher presented several convincing arguments, including the peculiarities of the functioning of this tune in the tradition (“memorized song”) and the strophic form with cross-rhyme, not typical of Udmurt ritual song folklore. Vereshchagin’s verses spread among people thanks to the Udmurt scholar, poet, and musician Kusebai Gerd. Gerd published this verse several times under the authorship of Vereshchagin, adding the refrain “Iz, iz, nunye, zarni bugore!” (Sleep, sleep, my child, golden ball!) after each stanza and replacing some words. In this version, the lullaby spread throughout Udmurtia. While in philological disputes the points of view of different parties are known, in ethnomusicology the problem of music authorship has not even been raised yet. The music was considered folk or attributed to Vereshchagin. The first musical notation of the lullaby with Vereshchagin’s lyrics was published in 1925, in a collection of Udmurt songs by Mikhail Romanov, who was a teacher at the Glazov Pedagogical Technical School. Apparently, he recorded it from his students, then reworked it for a four-voice choir. The lullaby was sung all over Udmurtia at that time. It was also sung by Gerd, who had a good voice and musical education. It can be assumed that Kusebai Gerd composed the melody to the verse of Vereshchagin. The fate of the verse “Chagyr, chagyr dydyke...” turned out to be fortunate. Vereshchagin nominated it as a lullaby song heard from an Udmurt woman “laying her child down”. And it really turned into a folk song, acquired its own melody, becoming known in every Udmurt village. Thus, in the Udmurt folklore genre system the author’s work acquired the legal status as an autonomous folklore unit, practically supplanting lullaby improvisations.